Primary actinomycosis of the big toe: a case report and literature review. Issue 11 (20th November 2019) - Almarzouq, Sawsan F; Almarghoub, Mohammed A; Almeshal, Obaid
Abstract: Actinomyces are Gram-positive branching bacteria that are part of the human gastrointestinal microflora. These organisms can cause actinomycosis, which is a slowly progressive suppurative infection involving the cervicofacial region. Primary involvement of extremities is very rare. Here, we present primary actinomycosis of the lower extremity and a review of related literature. A 35-year-old female from Al-Kharj City (agricultural area) presented to our plastic surgery clinic with complaints of a large mass on the left big toe that caused embarrassment and difficulty in wearing footwear. The patient underwent wide local excision and coverage of the big toe defect with Kutler bilateral V-Y advancement flaps. A high index of suspicion is required to diagnose actinomycosis in subacute or chronic inflammatory soft tissue lesions. Proper surgical intervention and antimicrobial are essential to treat the disease. We conclude that a high index of suspicion is required to diagnose actinomycosis in subacute or chronic inflammatory soft tissue lesions.